HUMAN PROBLEM IN PHILOSOPHY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Philosophy is one of the most ancient and complex branches of mankind, which deeply reflects on life, existence, knowledge, morality and the place of man. The problem of man is one of the central themes of philosophy, which examines the identity, purpose, moral issues and place of man in life. In the history of philosophy, the human problem has always been an effort, and each philosopher has to develop this problem from his own point of view.